Communicative Ethics as the Aura of Post-Postmodern Morality: A Study of Amy M. Homes’ This Book Will Save Your Life and Philip Roth’s Everyman - Fatemeh Esmaeili; Narges Montakhabi Bakhtvar; Farid Parvaneh (Critical Literary Studies)
In the postmodern era, there seems to be a pervasive decline of concept of ethics and community, leading to the devaluation of human life and moral values. The recent ethical turn in literary climate, however, has acknowledged a new version of ethics whose very quiddity needs further research. The present study aims to not only elucidate the moral codes of post-postmodern ethics, but also depict the significant role of communicative ethics, considered by the authors to be the infrastructure of the contemporary moral issues. Ergo, this article explores the theories of Habermas in two contemporary American novels in 2006, Amy M. Homes’ This Book Will Save Your Life and Philip Roth’s Everyman, so as to shed light on the resemblance of post-postmodern moral frames and Habermasian communicative ethics. Although the characters are initially illustrated in a postmodern setting with social alienation, solipsism, and instrumental actions, they undergo an ethical turn that is a manifestation of social and individual interactions, thus developing a cure and self-creation in the lives of the fractured characters. Finally, protagonists turn to be a self-satisfied and integrous people by maintaining the criteria of communicative ethics comprising the priority of well-being of others, empathy, and situational morality.